Analisis Faktor- Faktor yang Mempengaruhi Motivasi Belajar Bahasa Inggris Siswa di MA Plus Nurul Islam Sekarbela - Nur Hairunnisa’ Annuri; Dedi Riyan Rizaldi; Nurul Apriani; Nilwan; Ziadatul Fatimah (Lembaga Einstein College (LEC), 2025)
This study aims to identify and analyze the factors influencing students’ motivation in learning English and explain how these factors affect it at MA Plus Nurul Islam Sekarbela, Mataram. Using a qualitative case study design, data were collected from tenth-grade students through classroom observations, open-ended questionnaires, and semi-structured interviews. The findings revealed that a combination of intrinsic and extrinsic factors influences students’ motivation. Intrinsic factors include students’ awareness of the importance of English, personal goals, interest, and self-regulation strategies, which help them stay motivated despite difficulties. Extrinsic factors involve teachers’ roles, teaching methods, family support, peer influence, evaluation systems, and the utilization of media outside the class. Teachers’ interactive and enjoyable teaching styles were found to be the most influential in enhancing students’ enthusiasm, while excessive workload and strict attitudes decreased motivation. The study concludes that the dynamic interaction between internal drives and external support shapes English learning motivation